The Effect of Career Development, Organizational Commitment and Work Discipline on the Performance of Administrative Officials Equalized into Functional Positions in the Payakumbuh City Government - Vianora, Ade; Syafrizal, Syafrizal; Fatimah, Fatia (Universitas Pamulang, 2024)
The performance and management of apparatus resources continues to receive comprehensive and gradual improvements by prioritizing or being based on competency. One of the efforts made by the Payakumbuh City Government, West Sumatra Province, is implementing a policy of equalizing administrative positions into functional positions at the end of December 2021. Therefore, researchers are interested in analyzing the influence of career development, organizational commitment and work discipline on the performance of administrative officials which is equated to a functional position in the Payakumbuh City Government. This research is quantitative descriptive and uses Structural Model Assessment (SMA) hypothesis testing. Data collection was carried out by distributing questionnaires to 100 respondents. Sampling used the purposive sampling method. Hypothesis testing using SmartPLS. The research results show that: (1) career development partially has a positive and significant effect on performance; (2) organizational commitment partially has a positive and significant effect on performance; and (3) work discipline partially has a positive and significant effect on performance. Based on the results of this research, leaders need to adopt policies regarding increasing career development, work discipline and organizational commitment to optimize performance.